PENGARUH KOMISARIS INDEPENDEN DAN PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi pada Perusahaan Sub Sektor Makanan Olahan yang Terdaftar di Bursa Efek Indonesia (BEI) 2021-2025) - Nida Aisyatul Huda; M. Taufik Azis; Surono (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyse the influence of independent non-executive directors and profitability on Corporate Social Responsibility (CSR) disclosure in companies in the processed food sub-sector listed on the Indonesia Stock Exchange for the period 2021–2025. The study employs a quantitative approach based on Stakeholder Theory, involving 23 companies and 115 observations. CSR is measured using the CSRDI based on the GRI Standards 2021, independent directors are measured based on their proportion within the board of commissioners, and profitability is measured using the Net Profit Margin (NPM). The data were analysed using panel data regression with EViews 13 via the Random Effect Model. The results indicate that independent directors have a positive but non-significant effect, whilst profitability has a positive and significant effect on CSR disclosure. Taken together, both variables have a significant effect on CSR disclosure. An Adjusted R-squared value of 6.16% suggests that the variation in CSR disclosure is largely influenced by factors outside the model.